2011
DOI: 10.1002/sia.3627
|View full text |Cite
|
Sign up to set email alerts
|

Surface studies of halloysite nanotubes by XPS and ToF‐SIMS

Abstract: This report provides detailed experimental results of thermal and surface characterization on untreated and surface-treated halloysite nanotubes (HNTs) obtained from two geographic areas. Surface characterization techniques, including XPS and time-of-flight secondary ion mass spectrometry (ToF-SIMS) were used. ToF-SIMS surface analysis experiments were performed with both atomic and cluster ion beams. Higher ion yields and more high-mass ions were obtained with the cluster ion beams. Static ToF-SIMS spectra we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…According to the results of Table 2, the ratio of Si and Al in both of nanotubes, HNT and HNTBr, is greater than unity, which shows that the proportion of silicate is larger than the aluminate groups in the outer surface of halloysite [35]. Also, this value is larger in the case of HNT-Br which assigned to the presence of APTES groups on its surface.…”
Section: Synthesis Of Pdmaema-grafted Hntsmentioning
confidence: 68%
“…According to the results of Table 2, the ratio of Si and Al in both of nanotubes, HNT and HNTBr, is greater than unity, which shows that the proportion of silicate is larger than the aluminate groups in the outer surface of halloysite [35]. Also, this value is larger in the case of HNT-Br which assigned to the presence of APTES groups on its surface.…”
Section: Synthesis Of Pdmaema-grafted Hntsmentioning
confidence: 68%
“…Depending on different mining geographic areas, the lengths and diameters of the nanotubes can vary significantly [17]. SDS, which is an anionic surfactant, is a good dispersing agent for HNTs in aqueous solution [18]. With the addition of SDS, the HNT aqueous suspension was very uniform and stable and could last for a few days.…”
Section: Resultsmentioning
confidence: 99%
“…The first detailed study on the functionalisation of halloysite walls by cationic and anionic surfactants was performed by Ng et al (2011) on the other hand, showed significant levels of carbon and nitrogen on the external surface (Ng et al, 2011). The internal lumen of halloysite was hydrophobised with anionic perfluoro C5-C7 alkyl surfactants (Cavallaro et al, 2014).…”
Section: Surface Functionalisation Of Halloysite For Controlled Releasementioning
confidence: 99%